2016
DOI: 10.1002/hrdq.21248
|View full text |Cite
|
Sign up to set email alerts
|

Making the Invisible Visible: A Cross‐Sector Analysis of Gender‐Based Leadership Barriers

Abstract: Despite an abundance of educated, qualified women in the workforce, they continue to be underrepresented at the top of institutional leadership hierarchies. Theories of gendered organizations explain that work processes reproduce gendered structures of society in the workplace. These processes advantage men while forming barriers to women's success. This paper extends critical human resource development (HRD) theory by applying the concept of sexism hidden in the workplace to leadership and by outlining both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 41 publications
3
115
0
1
Order By: Relevance
“…Today researchers are finding that an awareness of unconscious bias can help leaders fundamentally rethink the way their organizations approach strategic decision making, organizational culture, inclusion, and talent management (Cook Ross Inc., ). As such, it should be a key element of women‐only leadership development programs (Bierema, ; Diehl & Dzubinski, ; Ely et al, ).…”
Section: Unconscious Gender Bias Theory and Researchmentioning
confidence: 99%
“…Today researchers are finding that an awareness of unconscious bias can help leaders fundamentally rethink the way their organizations approach strategic decision making, organizational culture, inclusion, and talent management (Cook Ross Inc., ). As such, it should be a key element of women‐only leadership development programs (Bierema, ; Diehl & Dzubinski, ; Ely et al, ).…”
Section: Unconscious Gender Bias Theory and Researchmentioning
confidence: 99%
“…Building upon the "mature" model of Bronfenbrenner (2009) Ecological Theory of Child Development, the theory offered by Egan and colleagues explores the interplay of influences at five levels: chrono, macro, exo, meso, and micro. Using a somewhat similar framework to examine influences that hinder women's leadership advancement, Diehl and Dzubinski (2016) offered descriptions of 27 types of gender-based leadership barriers, organizing them according to "the level of society in which they generally operate: macro (societal), meso (group or organizational), and micro (individual)" (p. 187). Notably, Diehl and Dzubinski observed that the challenges facing women in leadership cannot be targeted in isolation; rather, "the first step is to recognize that women encounter barriers at all three levels, and that macro and micro barriers impact women's ability to see themselves as leaders, as well as others' ability to consider them for leadership roles" (p. 199).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, participants struggled to reconcile the institutional view of an "ideal" woman with their own identities. The push and pull factors represent aspects of the literature of gendered leadership (Diehl and Dzubinski 2016;Egan et al 2017;Ibarra et al 2013;Kellerman and Rhode 2014), as well as circumstances unique to Christian higher education (Dahlvig and Longman 2016;Joeckel and Chesnes 2009;Reynolds 2014).…”
Section: Grounded Theory Modelmentioning
confidence: 99%
“…Worse, for women, essentialist beliefs can lead to self‐blame, rather than considering patriarchal social systems as the source of their difficulties (Scholz, ). Personalizing, or holding herself responsible for organizational challenges, (Diehl & Dzubinski, ) is a detrimental negative outcome of an essentialist mindset (Bohan, ; Scholz, ).…”
Section: Leadership and Gender Essentialismmentioning
confidence: 99%
“…Elsewhere we have described ourselves as equalists, meaning “we believe that all human beings, regardless of any socially defined identity category, are of equal value and deserve equal access, treatment, rights, opportunity, and freedom in all realms of society” (Diehl & Dzubinski, , p. 185). In this statement we acknowledge the reality of “socially defined identity categories” but argue that such categories should not form the basis of treatment for any individual member of society.…”
Section: Leadership and Gender Essentialismmentioning
confidence: 99%